Insurance and index-based disaster risk management workshop - CGIAR Research Program on Climate Change, Agriculture and Food Security (2014)
An effort to bring all potential partners and discuss the roles within a larger scheme for agriculture and climate risk management in Honduras. Photos: J.L.Urrea (CCAFS)